2018
DOI: 10.1093/mnrasl/sly229
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the dynamic state of galaxy clusters on segregation phenomena and velocity dispersion profiles

Abstract: In this work we investigate the influence of the dynamic state of galaxy clusters on segregation effects and velocity dispersion profiles (VDPs) for a sample of 111 clusters extracted from SDSS-DR7. We find that 73 clusters have Gaussian (G) velocity distribution and 38 clusters have a complex or non-Gaussian (NG) velocity distribution. We also split the G and NG samples into 'active' and 'passive' galaxies, according to their sSFRs and stellar masses. Our results indicate a strong spatial segregation between … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Such a trend is found to be steeper in highmass clusters than in low-mass clusters (Brown et al 2017;Yoon & Rosenberg 2015;Hess & Wilcots 2013;Woo et al 2013), more significant for low-mass galaxies than for high-mass galaxies (Woo et al 2017;Zhang et al 2013;Woo et al 2013;Wetzel et al 2013), consistent with the way that RPS is predicted to work. Later, it was found that galaxy properties also vary as function of radial velocity offsets from the cluster center at a given projected distance (Nascimento et al 2019;Bayliss et al 2017;Barsanti et al 2016;Mahajan et al 2011;Pimbblet et al 2006). With the aid of cosmological simulations, it becomes clear that positions on the PSD are associated with galaxies at different infall stages, thus show correlation with the averaged galactic properties (Haines et al 2015;Boselli et al 2014b;Gill et al 2005).…”
Section: Radial Extension Of Rps In the Massive Clustersmentioning
confidence: 99%
“…Such a trend is found to be steeper in highmass clusters than in low-mass clusters (Brown et al 2017;Yoon & Rosenberg 2015;Hess & Wilcots 2013;Woo et al 2013), more significant for low-mass galaxies than for high-mass galaxies (Woo et al 2017;Zhang et al 2013;Woo et al 2013;Wetzel et al 2013), consistent with the way that RPS is predicted to work. Later, it was found that galaxy properties also vary as function of radial velocity offsets from the cluster center at a given projected distance (Nascimento et al 2019;Bayliss et al 2017;Barsanti et al 2016;Mahajan et al 2011;Pimbblet et al 2006). With the aid of cosmological simulations, it becomes clear that positions on the PSD are associated with galaxies at different infall stages, thus show correlation with the averaged galactic properties (Haines et al 2015;Boselli et al 2014b;Gill et al 2005).…”
Section: Radial Extension Of Rps In the Massive Clustersmentioning
confidence: 99%
“…Menci & Fusco-Femiano 1996;Hou et al 2012;Pimbblet et al 2014;Bilton & Pimbblet 2018), presence of different spectral classes galaxies (Rood et al 1972) and cluster dynamical state (e.g. Hou et al 2009;Costa et al 2018;Nascimento et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…interactions (de Carvalho et al 2017) either prior, or during, off-axial mergers between two sub-clusters; the pronounced population of late-type galaxies on infall in merging environments as inferred by the blue sub-populations of galaxies gaining angular momentum r200, chiefly thought to be the result of galaxies with spiral morphology that have survived pre-processing (e.g. Cava et al 2017;Costa et al 2018;Bilton & Pimbblet 2018;Nascimento et al 2019). The study of rotational profiles would have been aided by the addition of understanding how different morphological sub-populations of cluster galaxies contributed to each of the colour profiles.…”
Section: Discussion and Summarymentioning
confidence: 99%